Autophagy and kidney inflammation - Kimura, Tomonori (Autophagy, 2017)
Inflammation plays a pivotal role in pathophysiological processes of kidney diseases. Macroautophagy/autophagy plays multiple roles in inflammatory responses, and the regulation of inflammation by autophagy has great potential as a treatment for damaged kidneys. A growing body of evidence suggests autophagy protects kidney from versatile kidney inflammatory insults, including those that are acute, chronic, metabolic, and aging-related. It is noteworthy that, in kidney, mitophagy is active, and damaged lysosomes are removed by autophagy. In this mode, autophagy suppresses inflammation to protect the kidney. Systemic inflammation also affects the kidney via pro-inflammatory cytokines and infiltration of inflammatory cells, and autophagy also has a regulatory role in systemic inflammation. This review focuses on the roles of autophagy in kidney diseases and aging through inflammation, and discusses the potential usage of autophagy as an inflammatory modulator for the treatment of kidney diseases.